Maternal Depressive Symptoms and Linguistic Input to Infants at High or Low Risk for Autism Spectrum Disorder - Lauze, Meghan S. (Tufts Archival Research Center, 2019)
A clinical psychology senior honors thesis completed at Tufts University and Boston Children's Hospital. Please contact meghan.lauze@gmail.com with any questions or to learn more information. One in every 59 children in the United States is diagnosed with Autism Spectrum Disorder (ASD). ASD can be accompanied by various behavioral, medical, and financial challenges, which may lead to elevated levels of daily stress and the onset of depressive symptoms in caregivers. Parental depression, in turn, has been associated with decreased quality and quantity of speech used with children. In my thesis research, I explore associations between depressive symptoms and linguistic input in a sample consisting of mothers of infant siblings at high and low risk of developing ASD. I first analyzed levels of depressive symptoms reported by these maternal groups and found that mothers of children with ASD reported significantly higher depressive symptoms when infant siblings were 12 months old. I then analyzed concurrent and prospective relations between maternal depressive symptoms and linguistic input used with infant siblings and found that depressive symptoms were predictive of fewer words used with infants. These results demonstrate a clear need to understand the relation between maternal mental health and children’s social development in all families, and especially in those where one or more children has a developmental disability.